Optimisation of reverse transcription-polymerase chain reaction for double stranded RNA extraction / Jamiila Ismail - Ismail, Jamiila (Faculty of Health Sciences, 2007)
The Reverse Transcription-Polymerase Chain Reaction (RT-PCR) have long been utilized by many researchers in converting ribonucleic acids (RNA) into complementary deoxyribonucleic acid (cDNA) in order to enable amplification to be done. Though it is a relatively simple and effective technique, it requires optimisation of parameters for each individual trial. In this study, optimisation of Reverse Transcription-Polymerase Chain Reaction was carried out using double stranded RNA rotavirus as a template. Rotaviral isolation and extraction was carried out on human stool samples that were previously confirmed positive for rotavirus antigen. Subsequently, cDNA synthesis was performed using MmULV-reverse transcriptase. Conventional Polymerase Chain Reaction (PCR) was then carried out followed by agarose gel electrophoresis, staining and finally visualisation of deoxyribonucleic acid (DNA) band using the gel documentation system. No amplification was seen in the first trial. Several attempts of optimisation were carried out: (1) titration of cDNA template prior polymerase chain reaction and (2) annealing temperature while other parameters were left constant. Nevertheless, the result showed no detectable band. It is suspected that other parameters affecting the amplification process was not optimised therefore contributing to bands failing to form. Among the parameters of yet to be optimised are Taq polymerase concentration, deoxynucleotide triphosphates (dNTPs) concentration, magnesium chloride concentration and number of PCR cycles. Since the primers were from referred journals, the denaturation and elongation temperature and time still remained the same. In conclusion, there are no specific set of procedures that can guarantee successful amplification without optimisation. All PCR parameters must be taken into account and optimised. Another important contribution is that contaminations must be avoided at all costs and the template being the most important factor as RNA are highly sensitive to exogenous and endogenous RNAses. The optimisation of this dsRNA is most difficult as compared to DNA or ssRNA because of the nature of the bonding in any dsRNA.